Characteristics of Wireless Vibration Sensors for South Aceh Polytechnic Building - Oktrison, Oktrison; Sipahutar, Erwinsyah; Jamsan, Firdaus; Candra, Rudi Arif; Ilham, Dirja Nur (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Vibration is a back-and-forth movement in a certain time interval that produces waves in a medium. Vibration can occur on a small or large scale. So on a small scale, a vibration sensor is needed to detect certain phenomena such as vibrations of engine capacity and detected pressure. On a large scale, vibration sensors can be used to detect earthquakes and other major phenomena and design a real-time vibration detection system for long distances, so vibration sensor components, controllers, and radio systems are needed. Therefore, researchers made a simple vibration detector using the experimental method. This final project aims to design, realize, and test the characteristics of the MPU 5060 accelerometer vibration sensor that is connected wirelessly. The characteristics of the sensor are tested against the magnitude of the vibration source, the distance of the vibration source, the placement medium, and the detection period. After testing the tool 10 times, it can be concluded that this simple vibration detector functions well and the highest average load results are obtained, namely in the 1-kilogram load test with a value of 1.93026 and the lowest average results are in the ceramic load test with a value of 0.651357.